2011
DOI: 10.1002/chem.201102488
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Electronic Consequences in Crafting Extended, π‐Conjugated, Light‐Harvesting Macrocycles

Abstract: The synthesis of a new series of free-base, Ni(II) and Zn(II) 2,3,12,13-tetra(ethynyl)-5,10,15,20-tetraphenyl porphyrins is described. Upon heating, two of the four ethynyl moieties undergo Bergman cyclization to afford the monocyclized 2,3-diethynyl-5,20-diphenylpiceno[10,11,12,13,14,15-jklmn]porphyrin in 30 %, 10 %, and trace yields, respectively. The structures of all products were investigated by using quantum chemical calculations and the free-base analogue was isolated and crystallized; all compounds sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…45,46 Later, the same group reported that the heating of 46 in the presence of PtCl 2 in toluene at 85-90 C gave a different fused product 47 (l max ¼ 610 nm in CH 2 Cl 2 ) in 35-48% yield (Scheme 11). 47,48 Richeter et al attempted the synthesis of N-heterocyclic carbene (NHC)-fused porphyrins by following the reaction route shown in Scheme 12. Tetrakis(4-tert-butylphenyl) Ni(II) porphyrin 51 was nitrated with LiNO 3 in a mixture of acetic acid and acetic anhydride to afford 52, which was reacted with 4-amino-4H-1,2,4-triazole to give 53.…”
Section: Porphyrins Fused To Aromatic Hydrocarbons and Heterocyclesmentioning
confidence: 99%
“…45,46 Later, the same group reported that the heating of 46 in the presence of PtCl 2 in toluene at 85-90 C gave a different fused product 47 (l max ¼ 610 nm in CH 2 Cl 2 ) in 35-48% yield (Scheme 11). 47,48 Richeter et al attempted the synthesis of N-heterocyclic carbene (NHC)-fused porphyrins by following the reaction route shown in Scheme 12. Tetrakis(4-tert-butylphenyl) Ni(II) porphyrin 51 was nitrated with LiNO 3 in a mixture of acetic acid and acetic anhydride to afford 52, which was reacted with 4-amino-4H-1,2,4-triazole to give 53.…”
Section: Porphyrins Fused To Aromatic Hydrocarbons and Heterocyclesmentioning
confidence: 99%
“…Porphyrins fused with aromatic units have attracted increasing attention owing to their intriguing optical and electronic properties and their applications in photodynamic therapy, two‐photon absorption, nonlinear optics, organic conducting materials, and photovoltaics . A variety of π‐expanded porphyrins have been synthesized (Scheme ), among which several multiply aromatic‐fused monomeric porphyrins such as quadruply phenylene‐fused porphyrin A , multiply phenylene‐fused porphyrin B , quadruply azulene‐fused porphyrin C , and quadruply anthracene‐fused porphyrin D , display remarkably red‐shifted absorption bands reaching at 1200, 750, 1300, and 1600 nm, respectively. However, repeatedly fused porphyrin in a laminated manner has remained quite rare because of synthetic difficulties.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the spin‐state control of thermal and photochemical Bergman reaction was reported for Pt(II)‐dialkynylporphyrin 62 . The thermal Bergman cyclization reactivity of 62 reveals a surprising reduction in the temperature at which the picenoporphyrin product is formed when compared to Zn(II) derivatives or the metal‐free 62 . Hoffman and co‐workers investigated the Bergman cyclization of osmaenediynes and rhodaenediynes 65 (Figure (b)).…”
Section: Metallo‐enediynesmentioning
confidence: 99%